Strategi Alokasi Anggaran Bantuan Sosial Untuk Penurunan Kemiskinan di Kabupaten Kulon Progo - Lestari, Meylani; Harianto, Harianto; Falatehan, A Faroby (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 2 (2022): Jurnal Manajemen Agribisnis, 2022)
Poverty is the problem in the economic development, the problem that to be the center of governments attention like in Kulon Progo Regency, the regency with the highest poverty rate at Special Region of Yogyakarta Province. The reducing poverty rate achievement in Kulon Progo Regency is under from the target listed in the 2017 th to 2022 nd Regional Medium-Term Development Plan (RPJMD). The social aid budget is a budget that directly related with the poverty reducing programs. Previous studies has shown that the social aid program is affecting the poverty reduction. This research aims to analyze the poverty spreads and the social aid budgets implementation, and this is for formulating the strategy of social aid budget allocations to reduce the poverty in Kulon Progo Regency. The results showed that the northern part of the regency where are dominated by highland, it has a higher poverty rate than the southern part of the district which is a coastal area. Wates and Pengasih subdistricts receive the largest allocations for social aid budget . The strategy is formulated by using IE matrix, SWOT matrix, and QSPM matrix which generate several alternatives priority strategies, that are encouraging the active role of stakeholders, and it is providing an accurate and specific integrated data on the social welfare of social aid recipients.